Plastic Injection Molding Process Analysis: Data Integration and Modeling for Improved Production Efficiency - Jose Isidro Hernández-Vega; Luis Alejandro Reynoso-Guajardo; Mario Carlos Gallardo-Morales; María Ernestina Macias-Arias; Amadeo Hernández; Nain de la Cruz; Jesús E. Soto-Soto; Carlos Hernández-Santos (Applied Sciences)
This paper presents a comprehensive analysis of the plastic injection molding process through the integration of data acquisition technologies and classification models. In collaboration with a company specializing in plastic injection, data were extracted directly from the machine during a specific period at the beginning of a shift change. These data were subjected to exploratory analysis to identify correlations between important variables, such as injection time, cycle time, and mold pressures. Additionally, classification models, including Random Forest and Logistic Regression, were constructed to predict and classify the process state based on these variables. The model results demonstrated high predictive performance, with 99.5% accuracy for Random Forest and 97% for Logistic Regression. These results provide a strong foundation for the early identification of potential problems and informed decision making to improve the efficiency of the plastic injection molding process. This study contributes to the advancement of the integration of intelligent technologies in industrial process optimization, aligned with the principles of Industry 4.0.